2015
DOI: 10.1002/anie.201409970
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular CH Activation through Gold(I)‐Catalyzed Reaction of Iodoalkynes

Abstract: The cycloisomerization reaction of 1-(iodoethynyl)-2-(1-methoxyalkyl)arenes and related 2-alkyl-substituted derivatives gives the corresponding 3-iodo-1-substituted-1H-indene under the catalytic influence of IPrAuNTf2 [IPr=1,3-bis(2,6-diisopropyl)phenylimidazol-2-ylidene; NTf2=bis(trifluoromethanesulfonyl)imidate]. The reaction takes place in 1,2-dichloroethane at 80 °C, and the addition of ttbp (2,4,6-tri-tert-butylpyrimidine) is beneficial to accomplish this new transformation in high yield. The overall reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…In 2015, Gonz alez utilized iodoalkynes in a similar reaction, using a gold catalyst to synthesize 3-iodoindenes via 1,5 CeH insertion. 62 Zhang and Hashmi independently reported the dual activation of aromatic diynes, 63 using a gold catalyst to access the intermediate gold vinylidene via a carbocyclisation route similar to that described by Harada. 56 Zhang reported the synthesis of a range of fused polycycles from diynes employing a strategy, which utilized the activation of both alkynes (Scheme 41).…”
Section: Metal Vinylidenesmentioning
confidence: 99%
“…In 2015, Gonz alez utilized iodoalkynes in a similar reaction, using a gold catalyst to synthesize 3-iodoindenes via 1,5 CeH insertion. 62 Zhang and Hashmi independently reported the dual activation of aromatic diynes, 63 using a gold catalyst to access the intermediate gold vinylidene via a carbocyclisation route similar to that described by Harada. 56 Zhang reported the synthesis of a range of fused polycycles from diynes employing a strategy, which utilized the activation of both alkynes (Scheme 41).…”
Section: Metal Vinylidenesmentioning
confidence: 99%
“…OEt 2 (0.5-2.0 equiv.) at room temperature, 3 a was obtained in 48-65% yield (entries [3][4][5]. Elevating the temperature in refluxing dichloromethane did not increase the yield (entry 6), and changing the solvents to THF, 1,4dioxane, and acetonitrile completely shut down the reaction (entries 7-9).…”
Section: Resultsmentioning
confidence: 99%
“…[2] Owing to the importance and synthetic utility of indenes, many approaches based on intra- [3] and intermolecular [4] cyclization reactions have been reported for their synthesis. The general approaches for preparing haloindenes include gold(I)-catalyzed intramolecular cyclization of iodo-functionalized alkynes, [5] iodonium-promoted cyclization of arylethynylmalonates, [6] palladium-catalyzed tandem reaction of 2-alkenylphenylacetylenes with CuX 2 (X=Cl, Br), [7] and reactions of o-(alkynyl)styrenes with NXS (X=I, Br). [8] However, there is no report on any direct approach for the synthesis of fluorine-containing indenes on the cyclopentadiene moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Gonza~lez et al successfully invented a distinct protocol for gold-catalyzed intramolecular CÀ H activation involving metal vinylidenes by replacing substituent from hydrogen to iodine on the parent alkyne (Scheme 41). [39] The reaction takes place in 1,2-dichloroethane at 80°C, in the presence of 5 mol% of catalyst, and the addition of ttbp (2,4,6-tri-tert-butylpyrimidine) is beneficial to accomplish this new transformation in high yields. They have studied this reaction in the presence of different catalysts and found that the presence of ttbp gave high yields.…”
Section: Gold-catalyzed Coupling Reactions Through Csp 2 à H Bond Actmentioning
confidence: 99%